Strangers Made Intimate: Ethnic Minority - Kinh Relationships in a Sino-Vietnam Border Commune (Case Study in Muong Khuong District, Lao Cai Province, Vietnam) - Vuong Ngoc Thi (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This article analyses the relationships between the ethnic minorities and the Kinh through the lens of “the stranger” theories. Via the testimonies of daily inter-ethnic encounters in a border commune in Muong Khuong district, Lao Cai city, it argues that putting the strangers in the intimate positions has been the cause of several ethnic minority - Kinh conflicts in their everyday encounters. Through the utility of “the stranger" theories, the article contributes to broadening the approach to ethnic relations in Vietnam and urges for more studies on contemporary ethnic conflicts, which demand new approaches and new solutions. Received 25th July 2022; Revised 10th September 2022; Accepted 29th September 2022